Synthesis Of Stimulants Based on Heterocyclic Compounds Quinazolin-4-One - Radjabova Gulmira Tadjinorovna; Saitkulov Foziljon Ergashevich (Zien Journals, 2024)
These compounds, by their nature, form five-membered and politic-membered complex compounds. Quinazolin-4-one and its homologues are of theoretical and practical importance among all heterocyclic compounds, and these compounds have high physiologically active properties among heterocyclic compounds, therefore, these compounds are used as herbicides, dyes, plant growth enhancers, stabilizers. used in obtaining
Keywords: Quinazolin-4-one; nature; complex compound